Green Intellectual Capital, Employee Innovativeness, Job Performance and Firms' Financial Performance: Evidence From SOEs in Indonesia - Darmansyah Darmansyah; Agung Dinarjito; Harnovinsah Harnovinsah (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Objectives: The aim of this research is to analyze the influence of green intellectual capital on job performance and financial performance with employee innovativeness as an intervening variable. Methods: This research is quantitative research using primary data taken through questionnaires. Respondents came from employees of BUMN/BUMN subsidiaries in the logistics services sector from top manager positions to staff. Results: The research results show that green intellectual capital has a direct positive effect on employee innovativeness, financial performance, and job performance. Employee innovativeness fails to mediate the relationship between green intellectual capital and job performance and financial performance. Implications: The implication of this research is that to achieve the goal of producing an organizational workforce that is high performing, innovative, and can improve the company's financial performance, policy makers and company management must adopt an employee-focused approach by implementing intellectual capital development in company employees. The results of this study state the same thing. The better the intellectual capital, the higher the employee innovativeness, job performance and financial performance. Therefore, the big step on the part of the employer is to develop and maintain intellectual capital that is constructive for the company and employees.